Preparation method of flexible fluorescence enhancement film of integrated microsphere lens array

Through the combination of solid-state microsphere self-assembly and PDMS, a flexible microlens array film with high refractive index is formed, which solves the problems of complex template production and low refractive index materials in the prior art, and achieves efficient fluorescence enhancement and single-particle imaging .

CN119241882APending Publication Date: 2025-01-03XUZHOU NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411607291.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing PDMS film microlens array preparation methods have complex template production processes and insufficient fluorescence enhancement effects caused by low refractive materials, which cannot be effectively used for single molecule or single particle imaging.

Method used

Solid-state microspheres are self-assembled to form an array structure and combined with polydimethylsiloxane (PDMS) prepolymers to form a flexible microlens array film by thermal curing, and use high refractive solid microspheres to enhance fluorescence excitation and collection Efficiency and anti-adsorption treatment to improve fluorescence enhancement performance.

Benefits of technology

A simplified preparation process is realized, the lens array size is flexibly controlled, the fluorescence excitation and collection efficiency is improved, and it can be combined with dry mirrors of low magnitude and low numerical aperture to obtain fluorescent images at the level of single particles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241882A_ABST
    Figure CN119241882A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a flexible fluorescence enhancement film integrated with a microsphere lens array, which comprises the following steps: dropwise adding a suspension of solid microspheres to the surface of a solid substrate, sucking away liquid, and self-assembling the microspheres to form an array structure; the preparation method comprises the following steps: uniformly mixing a monomer of polydimethylsiloxane with an initiator to form a prepolymer; coating a prepolymer on the surface of the plastic film, and heating and curing; and when the prepolymer is about to be cured into a film, covering the substrate on the surface of the film, continuously heating, and removing the substrate and the plastic film to form the flexible PDMS film integrated with the micro-lens array. The method is simple and reliable, the size of the lens array can be flexibly controlled, a template array is not needed, and the photoetching or injection molding process is avoided; and on the other hand, the lens is formed by the solid microspheres with high refractive index, so that the fluorescence excitation efficiency and the fluorescence collection efficiency of the lens on the fluorescent substances are enhanced, and a single-particle level fluorescent image is obtained by combining the lens with a dry lens with low magnification and low numerical aperture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a flexible fluorescence enhancement film integrated with a microball lens array, and belongs to the technical field of biochemical analysis and sensing. Background Art

[0002] Single-molecule or single-particle fluorescence imaging is a commonly used detection method in the field of biochemical analysis and sensing. Generally, fluorescent substances (dye molecules or nanoparticles) are used to label the target molecule or the complex of the target object, and the target molecule is quantified by the number of fluorescent spots. Since the fluorescence intensity emitted by a single fluorescent substance is weak, imaging and detecting fluorescent substances at the single-molecule or single-particle level requires the use of a high-magnification (greater than 60 times) and high numerical aperture (NA, greater than 0.8) oil objective, which requires manual focusing and imaging, and is difficult to automate and miniaturize. Low-magnification (less than 40 times) and low-NA (less than 0.7) dry objective for single-molecule or single-particle imaging must enhance the fluorescence emitted by a single fluorescent substance.

[0003] There are three main technologies for enhancing fluorescence intensity: surface plasmon resonance enhancement, photonic crystal enhancement, and microlens enhancement. Surface plasmon resonance enhancement, also known as metal enhancement, requires precise control of the distance between the fluorescent substance and the surface of the metal medium. If the distance is too close, it will lead to fluorescence quenching, and if the distance is too far, the enhancement effect will disappear. In addition, the metal layer is easily oxidized and has low stability. Photonic crystal enhancement technology requires fine processing of periodic micro-nano structures. The process is complex and difficult to process. In addition, the fluorescent substance falls in different areas of the photonic crystal structure, resulting in large differences in enhancement. Microlens enhancement technology can not only increase the intensity of the excitation light, but also enhance the collection efficiency of fluorescence, and can perform light field modulation, which has good application potential.

[0004] At present, there are two main forms of microlens array processing based on PDMS membrane, injection molding technology and photolithography technology. The former requires first processing a mold with a lens shape, injecting PDMS into the mold, and heating it to form. The latter uses photolithography technology to process a microstructure array template on a substrate, and after multiple replications, a PDMS microlens array is formed. Both injection molding and photolithography technology require complex processing processes, and the size and spacing of the lens array are consistent with the template and cannot be flexibly adjusted. On the other hand, the lens material is generally plastic, and the refractive index of the material is small (less than 1.5), resulting in insufficient light collection ability of the microlens, and it is impossible to use a low-magnification and low-NA dry lens to image a single fluorescent substance, limiting the application of microlens arrays in the field of single molecule and single particle imaging. Therefore, it is necessary to develop a method for preparing microlens arrays of high refractive index materials.

[0005] At present, the preparation method of PDMS thin film microlens has the following two technical problems: (1) PDMS thin film microlens array requires a complex template production process, which is costly and has low reliability; (2) The light collection ability of low refractive index microlenses is limited and the fluorescence enhancement effect is weak. Even when combined with a low-magnification and low-NA dry lens, it is impossible to obtain the image of a single fluorescent substance. Summary of the invention

[0006] The present invention aims at solving the technical problems in the prior art and provides a method for preparing a flexible fluorescence enhancement film with an integrated microsphere lens array.

[0007] The present invention provides a method for preparing a flexible fluorescence enhancement film integrated with a microsphere lens array, comprising the following steps: Step 1: drop a suspension of solid microspheres onto the surface of a solid substrate, and slowly absorb the liquid using a pipette, so that the microspheres self-assemble on the surface of the solid substrate to form an array structure; Step 2: Evenly mix the monomer of polydimethylsiloxane (PDMS) and the initiator in a certain volume ratio, degas, and form a prepolymer; apply a certain thickness of the prepolymer on the surface of the plastic film, and heat and cure; Step 3: When the prepolymer is about to solidify into a film, the microsphere array substrate prepared in step 1 is covered on the surface of the film, and the prepolymer is heated until it is completely solidified, and then the top substrate and the bottom plastic film are removed to form a flexible PDMS film with an integrated microlens array; Step 4: Perform anti-adsorption treatment on the flexible PDMS film, take fluorescent dye molecules as the object, characterize the fluorescence enhancement performance of the film at the macro level, take fluorescent nanoparticles as the object, characterize the fluorescence enhancement performance of the film at the single particle level.

[0008] The technical solution further optimized as the present invention is as follows: In the step 1, the solid microspheres are one of polystyrene, titanium dioxide, barium titanate, and silicon dioxide, the refractive index of the solid microspheres is 1.5 to 2.5, and the size of the solid microspheres is 5 to 500 microns.

[0009] Preferably, the solid microspheres are made of barium titanate, have a refractive index of 1.9, and a size between 140 and 150 microns.

[0010] In step 2, the volume ratio of the polydimethylsiloxane monomer to the initiator is 0.2 to 10, the material of the plastic film is one of polystyrene, polycarbonate, polymethacrylate, polyethylene terephthalate, and polyurethane, the coating thickness of the prepolymer is 0.2 to 5 mm, and the heating and curing temperature is 40 to 100°C.

[0011] Preferably, the volume ratio of the polydimethylsiloxane monomer to the initiator is 10:1.

[0012] In step 4, the reagent for the anti-adsorption treatment is a silanization reagent modified with a long-chain polymer, and its mass concentration is between 0.5% and 20%. The treatment time is between 1 minute and 60 minutes. The anti-adsorption treatment process includes surface activation and surface modification. A silane film can be formed on the surface of the material to reduce the nonspecific adsorption of PDMS.

[0013] Preferably, the polymer long chain is at least one of polyvinyl alcohol, polyethylene glycol monomethyl ether and dextran, and its molecular weight is between 1 kDa and 500 kDa.

[0014] In step 4, the fluorescent dye molecule is at least one of fluorescein sodium and its derivatives, rhodamine B and its derivatives, Cy3, Cy5, and FAM, and the fluorescent nanoparticles are fluorescent materials with a size of less than 500 nm, including at least one of quantum dots, carbon dots, gold clusters, silver clusters, upconversion particles, fluorescent polystyrene spheres, and fluorescent silica spheres.

[0015] Preferably, the polymer long chain modified silanization agent is mPEG-silane, the molecular weight of the polymer long chain is 5 kDa, the mass concentration is 2.5% to 20%, and the treatment time is 5 minutes to 20 minutes; the fluorescent dye molecule is rhodamine B, and the fluorescent nanoparticles are quantum dots.

[0016] In the step 2, the heating and curing time when the prepolymer is about to be cured into a film is 10 to 12 minutes; in the step 3, the heating time when the prepolymer is continuously heated until it is completely cured is 18 to 20 minutes.

[0017] Compared with the prior art, the preparation method of the present invention is simple and reliable, can flexibly control the size of the lens array, does not require a template array, and avoids the photolithography or injection molding process; on the other hand, the present invention forms a lens with solid microspheres with a high refractive index, which enhances the fluorescence excitation efficiency and fluorescence collection efficiency of the lens for fluorescent substances, and is combined with a low-magnification and low-numerical aperture dry lens to obtain fluorescent images at the single-particle level. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The figure is a schematic diagram of the manufacturing process of the flexible fluorescence enhancement film with integrated microlens array in the present invention.

[0019] Figure 2 This is a scanning electron microscope (SEM) image of the integrated microlens array film of the present invention.

[0020] Figure 3 This is a diagram showing the anti-adsorption effect of the film after treatment with 10% mPEG-silane (5kDa) for 10 minutes in the present invention.

[0021] Figure 4 This is a graph showing the anti-adsorption results of the film treated with mPEG-silane (5 kDa) at different concentrations for 10 minutes in the present invention.

[0022] Figure 5 This is a graph showing the anti-adsorption effect of 10% mPEG-silane (5 kDa) on the film at different treatment times in the present invention.

[0023] Figure 6 This is a diagram showing the adsorption effect of the untreated film of the present invention.

[0024] Figure 7 Prepare a flow chart for quantum dot imaging in the present invention.

[0025] Figure 8 This is a fluorescence image of the integrated microlens array film (with a concentration of 50 pM) covered on the quantum dots, taken by the 20x objective lens of the fluorescence inverted microscope in the present invention in combination with a CMOS camera.

[0026] Fig. 9 This is a fluorescent image of the coverslip above the quantum dots taken by the 20x objective lens of the fluorescence inverted microscope combined with a CMOS camera in the present invention.

[0027] Fig.10 This is a superposition effect diagram of multi-frame fluorescence images of quantum dots taken by a 20x objective lens (NA=0.45) combined with a CMOS camera in the present invention.

[0028] Fig.11 This is a curve diagram showing the intensity of a single fluorescent spot changing with time in the present invention.

[0029] Fig.12 The film-enhanced Rhodamine B solution (concentration 1x10 -7 M) Fluorescence image.

[0030] Fig.13 This is the unenhanced Rhodamine B solution (concentration 1x10 -7 M) Fluorescence image.

[0031] Fig.14 The microlens array film of the present invention is subjected to a Rhodamine B solution (concentration of 1x10 -7 M) Schematic diagram of fluorescence enhancement data. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and specific operation process are given, but the protection authority of the present invention is not limited to the following embodiments. Example 1 Preparation of flexible fluorescence enhancement film with integrated microsphere lens array

[0033] The film preparation process is as follows Figure 1 As shown, a certain amount of barium titanate microspheres are dissolved in deionized water to form a microsphere suspension. The refractive index of barium titanate microspheres is 1.9, and the size is between 140 and 150 microns. 10 microliters of microsphere suspension is added to the surface of the coverslip, and the liquid is slowly sucked away with a pipette. The reduction of liquid will induce the microspheres to self-assemble on the surface of the coverslip to form a microsphere array structure. The monomer of PDMS is mixed with an initiator (SYLGARD TM 184 Silicone Elastomer Curing Agent) is mixed evenly in a volume ratio of 10:1 (v / v), placed in a vacuum dryer for degassing to form a prepolymer; the prepolymer is poured onto the surface of a plastic film (the material of the plastic film is polyethylene terephthalate), and placed on a coater for coating, with a coating thickness of 1 mm, and then the coated prepolymer and film are transferred to an electric heating plate together, and heated and cured at 80°C for 10-12 minutes. At this time, a cover glass carrying a microsphere array is covered on the surface of the PDMS coating, and gravity is applied to cause the microspheres to partially embed into the PDMS coating. The cover glass is removed and continued to heat until the coating is completely cured. The general heating time is 18-20 minutes to form a PDMS film with an integrated microlens array (see Figure 2 ). The film has good flexibility and ductility, and can be bent, folded, stretched and other operations. After the external force field is released, the film can return to its original shape. Example 2 Film anti-adsorption treatment and fluorescence enhancement effect test

[0034] Take 10 mg of mPEG (5kDa) modified silane and dissolve it in 100 ul dimethyl sulfoxide to form PEG-silane with a concentration of 10% (w / v). Use a hole puncher to make a through hole with a diameter of 3.5 mm on the PDMS block, reversibly seal the PDMS block with the through hole with the film of the integrated microlens array, and align the through hole position with the microlens array to form a micropool, and the microlens array is located at the bottom of the micropool. Add 10 microliters of 10% (w / v) PEG-silane into the micropool, incubate for 10 minutes, remove the liquid, and complete the anti-adsorption treatment.

[0035] A certain volume of 8 nM quantum dot stock solution (CdSe / ZnS core-shell quantum dots, QD655, Thermo Fisher Scientific) was mixed with different volumes of PBS buffer (pH=7.4) to form quantum dot solutions with final concentrations of 50pM and 10pM. 10 microliters of quantum dot solution (10pM) was added dropwise to the microcell after anti-adsorption treatment, incubated for 20 minutes, the solution was removed, and the PBS buffer (pH=7.4) was used to wash three times. The upper PDMS block was peeled off, and then the film was placed on the stage of a fluorescence microscope. The quantum dot adsorption was observed with a 100x objective lens. The fluorescence imaging results are shown in Figure 2. Figure 3 The adsorption amount of quantum dots on the microlens array film is affected by the concentration and treatment time of PEG-silane. 0%, 2.5%, 5.0%, 7.5%, 10% and 20% (w / v) PEG-silane were used for anti-adsorption treatment, and the treatment time was fixed at 10 minutes. The adsorption amount of quantum dots is shown in Figure 4 The concentration of PEG-silane was fixed at 10%, and the treatment was performed for 0, 5, 10, 15 and 20 minutes respectively. The results are shown in Figure 5 As shown. The experiment showed that the best anti-adsorption effect was achieved when 10% (w / v) mPEG-silane was treated for 10 minutes. Figure 3 ) is significantly lower than that of the film without anti-adsorption treatment (see Figure 6 ).

[0036] The clean glass slide was immersed in a 1% (v / v) polydimethyl ammonium chloride solution for 12 hours to form a glass slide with a positive surface charge. 2.5 μl of quantum dot solution (50 pM) was added to the positively charged glass slide, and the integrated microlens array film was covered on the top of the quantum dot solution and allowed to stand for 20 minutes (see Figure 7 ), and then the assembly was transferred to the stage of a fluorescence microscope and observed under a 20x dry lens (NA = 0.45). A CMOS camera (DV887, Andor Technology, USA) was used to capture the fluorescence image, and clear fluorescent spots could be seen, such as Figure 8 When the integrated microlens array film was replaced with a clean cover glass, no fluorescent spots appeared in the fluorescence image under the same conditions (see Fig. 9 ), which proves that the microlens array film has a significant fluorescence enhancement effect.

[0037] The quantum dots were prepared using the above steps, and a 20x dry lens (NA = 0.45) was used in conjunction with a CMOS camera to continuously capture multiple frames of fluorescence images of the same area, and the fluorescence intensity of a fixed fluorescent spot in the image was analyzed (see Fig.10 ). The curve of the fluorescence intensity of the fluorescent spot changing with time is shown in Fig.11As shown. The fluorescent dot has the unique periodic change of fluorescence light-darkness of quantum dots, that is, the "blinking" phenomenon of quantum dots, and when the observation time is greater than 100 seconds, the fluorescence of the fluorescent dot disappears, indicating that the quantum dot is bleached by continuous light. The fluorescence intensity-time curve is basically consistent with the photobleaching curve characteristics of a single quantum dot, confirming that the fluorescent light spot we observed is the fluorescence emitted by a single quantum dot.

[0038] A certain amount of rhodamine B (RhB, Tianjin Xienen Biochemical Technology Co., Ltd., China) was mixed with a certain volume of ultrapure water to form a final concentration of 1x10 -7 M rhodamine B solution. Take 10 mg of mPEG (5kDa) modified silane and dissolve it in 100ul dimethyl sulfoxide to form a PEG-silane concentration of 10%. Use a hole puncher to make a through hole with a diameter of 3.5mm on the PDMS block, reversibly seal the PDMS block with the through hole with a clean glass slide, drop 20 microliters of 10% (w / v) PEG-silane into the through hole, incubate for 10 minutes, remove the liquid, and complete the anti-adsorption treatment. Add 20 microliters of rhodamine B solution (5x10 -7 M) was dripped onto the microcell after anti-adsorption treatment, and the integrated microlens array film after anti-adsorption treatment was covered on the microcell. The assembly was then transferred to the stage of a fluorescence microscope and observed under a 20x dry lens (NA = 0.45). A CMOS camera (DV887, Andor Technology, USA) was used to capture the fluorescence image. The integrated microlens array film was replaced with a clean cover glass, and the fluorescence image was observed and captured under the same conditions. It was found that the fluorescence image of the microlens array area (see Fig.12 ) than the fluorescence image of the clean coverslip area (see Fig.13 ) is brighter, and the fluorescence intensity is measured to be 4.7 times stronger (see Fig.14 ), which proves that the microlens array film has a significant fluorescence enhancement effect.

[0039] The above description is only a specific implementation of the present invention, but the protection scope of the present invention is not limited thereto. Any person familiar with the technology can understand and think of any changes or substitutions within the technical scope disclosed by the present invention, which should be included in the scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a flexible fluorescence enhancement film with an integrated microsphere lens array, characterized in that: The following steps are involved: Step 1, dropping a suspension of solid microspheres onto the surface of a solid substrate, and the microspheres self-assemble on the surface of the solid substrate to form an array structure; Step 2, uniformly mixing the monomer of polydimethylsiloxane and the initiator in a certain volume ratio, degassing, and forming a prepolymer; coating the prepolymer with a certain thickness on the surface of the plastic film, and heating and curing; Step 3: When the prepolymer is about to solidify into a film, the microsphere array substrate prepared in step 1 is covered on the surface of the film, and the prepolymer is heated until it is completely solidified, and then the top substrate and the bottom plastic film are removed to form a flexible PDMS film with an integrated microlens array; Step 4: Perform anti-adsorption treatment on the flexible PDMS film, take fluorescent dye molecules as the object, characterize the fluorescence enhancement performance of the film at the macro level, take fluorescent nanoparticles as the object, characterize the fluorescence enhancement performance of the film at the single particle level.

2. The method for preparing the flexible fluorescence enhancement film with integrated microsphere lens array according to claim 1, characterized in that: In the step 1, the solid microspheres are one of polystyrene, titanium dioxide, barium titanate, and silicon dioxide, the refractive index of the solid microspheres is 1.5 to 2.5, and the size of the solid microspheres is 5 to 500 microns.

3. The method for preparing the flexible fluorescence enhancement film with integrated microsphere lens array according to claim 1, characterized in that: In step 2, the volume ratio of the polydimethylsiloxane monomer to the initiator is 0.2 to 10, the material of the plastic film is one of polystyrene, polycarbonate, polymethacrylate, polyethylene terephthalate, and polyurethane, the coating thickness of the prepolymer is 0.2 to 5 mm, and the heating and curing temperature is 40 to 100°C.

4. The method for preparing the flexible fluorescence enhancement film with integrated microsphere lens array according to claim 1, characterized in that: In step 4, the anti-adsorption treatment reagent is a polymer long-chain modified silanization reagent, the mass concentration of which is 0.5% to 20%, and the treatment time is 1 minute to 60 minutes.

5. The method for preparing the flexible fluorescence enhancement film with integrated microsphere lens array according to claim 4, characterized in that: The polymer long chain is at least one of polyvinyl alcohol, polyethylene glycol monomethyl ether and dextran, and its molecular weight is between 1 kDa and 500 kDa.

6. The method for preparing the flexible fluorescence enhancement film with integrated microsphere lens array according to claim 1, characterized in that: In step 4, the fluorescent dye molecule is at least one of fluorescein sodium and its derivatives, rhodamine B and its derivatives, Cy3, Cy5, and FAM, and the fluorescent nanoparticles are fluorescent materials with a size of less than 500 nm, including at least one of quantum dots, carbon dots, gold clusters, silver clusters, upconversion particles, fluorescent polystyrene spheres, and fluorescent silica spheres.

7. The method for preparing the flexible fluorescence enhancement film with integrated microsphere lens array according to claim 1, characterized in that: In the step 2, the heating and curing time when the prepolymer is about to be cured into a film is 10 to 12 minutes; in the step 3, the heating time when the prepolymer is continuously heated until it is completely cured is 18 to 20 minutes.